PENGARUH TIME RESTRICTED FEEDING (TRF) TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI - Novita Aryani; Friska Margaretha Parapat (Jurnal Online Keperawatan Indonesia, 2020)
Hypertension is a chronic condition characterized by an increase in systolic blood pressure> 140 mmHg and diastole> 90 mmHg. This condition can damage blood vessels and interfere with blood flow, causing degenerative diseases to death. Time Restricted Feeding (TRF) is a form of intermittent fasting that regulates eating patterns by applying a cycle model of 12-16 hours of fasting and another 8-12 hours of non-fasting. TRF fasting follows the circadian rhythm pattern of the human body light-dark (eat-fast). This study aims to determine the effect of TFR on reducing blood pressure in hypertensive patients. This research is a quantitative study using a quasy experimental design with a non-equivalent control group approach, with the population being hypertensive patients living in 2 and 5 neighborhoods of Helvetia Village, sampling by means of purposive sampling with 32 respondents divided into intervention and control groups. . Respondents did TRF fasting for 30 days with a span of 12 hours of fasting starting after dinner while still allowed to drink mineral water. There are no restrictions on calories or types of food when the respondent is not fasting. The results of the study after the Wilcoxon test showed that systolic blood pressure in the intervention group decreased by 11.12 mmHg with a value of p = 0.003 (p <0.05) and diastolic blood pressure decreased by 5.19 mmHg with a value of p = 0.003 (<0.05) compared to the control group. TRF fasting follows the circadian rhythm pattern of the human body light-dark (eat-fast) so it is very good for people with hypertension The conclusion of this study is that there is an effect of TRF fasting on lowering blood pressure in hypertensive patients.